Hematological Parameters and Liver Function After COVID-19 Vaccination ( Simple Population Patients in Ramadi City – Iraq): Parameter Hematologi dan Fungsi Hati Setelah Vaksinasi COVID-19 (Populasi Sederhana Pasien di Kota Ramadi - Irak) - Ridhab Ajeel Jasim; Saif Subhi Noori; Adeeb Shakir Mahmood; Asmaa Wajeh Jumaa; Fatin Zuher Abd Alkareem (Academia Open, 2023)
This study aimed to investigate the influence of COVID-19 vaccination on liver function and blood parameters, specifically Mean Corpuscular Volume (MCV) and Hemoglobin (HGB) levels, among young adults (aged 18-32) in Anbar province. Blood samples from 50 individuals were collected at Ramadi Teaching Hospital, with half of the participants vaccinated and the other half unvaccinated. Results revealed a significant decrease in MCV and HGB levels among the vaccinated group compared to the unvaccinated group. Concurrently, liver function indicators, including Alanine Aminotransferase (ALT), Alkaline Phosphatase (ALP), and Bilirubin, showed a marked increase in the vaccinated individuals, indicating potential hematological disorders and liver injury. These findings underscore the importance of COVID-19 vaccination while highlighting the need for continued monitoring of liver health and blood parameters in vaccinated individuals to mitigate potential long-term health implications. Highlights: COVID-19 vaccination in young adults may lead to a significant decrease in Mean Corpuscular Volume (MCV) and Hemoglobin (HGB) levels. Liver function indicators such as Alanine Aminotransferase (ALT), Alkaline Phosphatase (ALP), and Bilirubin exhibit a notable increase in vaccinated individuals. Continuous monitoring of liver health and blood parameters is crucial for assessing potential long-term health implications associated with COVID-19 vaccination. Keywords: COVID-19 Vaccination, Liver Function, Blood Parameters, Young Adults, Anbar Province.